Implementation of Integrated Problem-Based Learning and Storytelling Technique on Learning Outcomes and Attitudes Towards Chemistry - Yunita Arian Sani Anwar; Syarifa Wahidah Al Idrus; Eka Junaidi (Jurnal Pendidikan Progresif, 2024)
Implementation of Integrated Problem-Based Learning and Storytelling Technique on Learning Outcomes and Attitudes Towards Chemistry. Objective: This study aims to analyze the effect of problem-based learning (PBL) integrated with storytelling on learning outcomes and attitudes towards chemistry in basic chemistry courses. Methods: This experimental study employed a pretest-post-test control group design. The sample consisted of 99 new students from the Faculty of Agricultural Technology enrolled in basic chemistry courses, with 49 students in the experimental group and 50 in the control group. The research instruments included a critical thinking test with 15 validated multiple-choice questions (Cronbach's alpha = 0.817) and an attitude towards chemistry instrument based on four categories (Cronbach's alpha = 0.765). Data analysis was performed using MANOVA. Results: The results showed that the N-gain of student learning outcomes was higher in the experimental group compared to the control group. Similarly, students' attitudes towards chemistry in the experimental group, which received PBL with storytelling integration, were higher in all categories than those in the control group. The highest attitude scores in the experimental group were in the categories of attitude towards chemistry material and confidence in learning chemistry, while the lowest score was in the category of attitude towards chemistry laboratory work. In the control group, the highest score was in the category of the tendency to learn chemistry, with the lowest score matching the experimental group's lowest category. The MANOVA test indicated a significant effect of PBL with storytelling integration on both learning outcomes and attitudes towards chemistry. Conclusion: Implementing problem-based learning integrated with storytelling in basic chemistry courses positively influences learning outcomes and attitudes towards chemistry, with the experimental group showing better results compared to the control group. Keywords: attitudes towards chemistry, critical thinking, storytelling, problem based learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202477